Effects of fungal- and plant-derived non-starch polysaccharides in macrophages - Castro-Alves, Victor Costa (2017)
The consumption of fungal- and plant-derived non-starch polysaccharides (NSP) have been associated with reduced risk of cardiovascular diseases and cancer. In addition to promote physiochemical effects on the gastrointestinal tract and serve as substrate for the intestinal microbiota to produce short-chain fatty acids, NSP can interact with immune system cells including macrophages, which are crucial for tissue repair, lipid metabolism and host defense against foreign substances and pathogens. However, the effects of NSP in macrophages depends on their structure. Recently, it was showed that the chayote (Sechium edule) and the fungus Pleurotus albidus are promising sources of NSP with potential immunomodulatory effects in macrophages. In this study, it was explored the effects of cooking on the composition of NSP from chayote and evaluated their biological effects in macrophages. Furthermore, it was optimized a method for the extraction of mushroom NSP and characterized the structure and biological effects of NSP from P. albidus in macrophages. Results showed that the NSP from chayote pulp regulate cytokine secretion and phagocytosis by macrophages, and minor changes in composition during cooking influences their effects in macrophages. Furthermore, NSP from chayote induces cholesterol efflux and inhibits the expression of genes required for NLRP3 inflammasome activation in macrophages previously exposed to cholesterol crystals. Then, it was showed that the optimized method for the extraction of NSP from mushroom reduces by up to half the extraction time commonly required. Furthermore, results showed that P. albidus is source of easily extractable glucans with biological effects in macrophages. Results also suggest that glucans from P. albidus inhibit lipid-induced inflammation and foam-cell formation at distinct levels, with significant effects on NLRP3 inflammasome activation. Taken together, the results suggest that the benefits of chayote NSP is beyond their physical properties on the gastrointestinal tract, and that the P. albidus NSP offers potential health benefits that might be of relevance as a functional food ingredient.